Mycotic aortic arch aneurysm coexistent with constrictive pericarditis: is surgery a dangerous resort? - Yu, Peter S. Y.; Yu, Simon C. H.; Chu, Cheuk-Man; Kwok, Micky W. T.; Lam, Yuk-Hoi; Underwood, Malcolm J.; Wong, Randolph H. L. (Journal of Thoracic Disease, 2016)
An elderly man presented with fever and evidence of Salmonella infection, and was diagnosed to have coexisting constrictive pericarditis and mycotic aneurysm of the aortic arch. Pericardiectomy was performed under cardiopulmonary bypass with good result. To avoid deep hypothermic circulatory arrest, an aorto-brachiocephalic bypass, instead of total arch replacement, was performed. This was followed by a staged carotid-carotid bypass, thoracic endovascular stent graft placement. He was subsequently treated with prolonged antibiotics, and inflammatory marker normalized afterwards. He was last seen well 2 years after the operation. Follow-up computer tomography (CT) scan at 18 months post-op showed no evidence of endoleak or fistulation. Our case demonstrated that a hybrid treatment of open pericardiectomy and aortic debranching followed by thoracic endovascular stent graft placement is feasible and associated with satisfactory mid-term outcome.